Peradaban Manusia Pasca Nuh AS - Isa Barid; Rangga Umbara K (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2016)
The civilization of mankind was originally one convenient with the origin of the creation of man from one (Adam as.), developed into two, three and so on. History records, the spread of human civilization originated from the descendants of Noah as., the second father of mankind. Through Sam who became the ancestor of the Arabs, the Ham of the African nation and the Yafits of the European nation, human civilization continues to grow to become hundreds. This paper follows the history of the spread of human civilization and presents analyzes of the achievements of its civilization, so it seems clear later why human civilization in Arabia is different from Europe and Africa, caused by differences in the challenges of situations and conditions in different places. From here it appears that diversity, diversity and diversity are biological children born of the history of human civilization.